2012
DOI: 10.1007/s11250-012-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular investigation of Newcastle disease in household chicken flocks and associated markets in Eastern Shewa zone, Ethiopia

Abstract: Cross-sectional surveys for Newcastle disease (ND) were conducted in non-vaccinated household flocks of village chickens to assess the serological and virological ND status in households and associated live bird markets. In total 1899 sera and 460 pools of cloacal and tracheal swabs were sampled and tested using a commercial enzyme-linked immunosorbent assay (ELISA) and real time reverse transcriptase polymerase chain reaction (rRT-PCR), respectively. Additionally, paired cloacal and tracheal swabs from 1269 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
3
33
3
Order By: Relevance
“…In total, 8.4% of the swab samples were positive for NDV of which 38.5% were virulent strains. The finding is in agreement with earlier studies which revealed the circulation of virulent strains of NDV in village chickens in Ethiopia [18,19]. The first documented evidence of ND in Ethiopia dates back to 1978 when an outbreak occurred in Eritrea, the then, Northern part of the country.…”
Section: Discussionsupporting
confidence: 92%
“…In total, 8.4% of the swab samples were positive for NDV of which 38.5% were virulent strains. The finding is in agreement with earlier studies which revealed the circulation of virulent strains of NDV in village chickens in Ethiopia [18,19]. The first documented evidence of ND in Ethiopia dates back to 1978 when an outbreak occurred in Eritrea, the then, Northern part of the country.…”
Section: Discussionsupporting
confidence: 92%
“…1999;Alexander and Senne, 2008). Also, its inestimable impact on food security is a course for concern due to the reduction in dietary protein supply mostly in developing countries (Aboe et al, 2006;Saidu et al, 2006;Olabode et al, 2008;Chaka et al, 2012;Solomon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These cause direct losses also interact with bacteria such as Mycoplasma gallisepticum (Mg) and Mycoplasma synoviae (Ms), which exacerbate respiratory diseases. Serology shows ND is widespread throughout Ethiopia (Tadesse et al 2005; Zeleke et al 2005; Regasa et al 2007; Mazengia et al 2010; Chaka et al 2012), and virulent and lentogenic strains have been isolated (Chaka et al 2013; Fentie et al 2014). Vaccines, produced locally, are used in commercial farms, multiplication centres (Dessie and Jobre 2004) and more recently in field trials for village birds (Nega et al 2012).…”
Section: Introductionmentioning
confidence: 99%